Drug Utilization Evaluation of Antibiotics in an Indian Hospital Setting: A Prospective Observational Study - Nyamagoud, Sanatkumar Bharamu; Totar, Laxmi Bhimappa; Yadav, Hema; Ahamed, S M Shoaib; Achyut, Khandke Shruti; Vanasakrithmath, Vaishanavi; Ranjani, R; Bantanur, Tanushree R; Naik, Chandan Ashok; Mathapati, Shivani; Lakkannavar, Spoorthi G; Karthik, K H (International Journal of Pharmaceutical Investigation, 2026)
Background Rational drug use is essential to improving healthcare outcomes and minimizing risks such as antimicrobial resistance. This study evaluates prescription patterns in the General Medicine Department of an Indian hospital in alignment with WHO prescribing guidelines. Objectives To assess drug utilization trends, particularly focusing on antibiotic use, polypharmacy, and injection practices, and to identify areas needing intervention. Materials and Methods A prospective observational study was conducted involving 212 inpatients. Prescription data were analyzed for adherence to WHO indicators, including the number of drugs per prescription, generic prescribing, use of essential medicines, antibiotic utilization, and injection frequency. Results The average number of drugs per prescription was 6.01, exceeding WHO recommendations and indicating significant polypharmacy. The overuse of antibiotics, accounted for 41.73% and injections were 29.10%. Suggesting potential overuse. Generic prescribing stood at 56.63%, while only 44.62% of drugs were from the Essential Drugs List. Conclusion The findings highlight concerns in prescribing practices, especially polypharmacy and overuse of antibiotics and injections. Strategies such as antimicrobial stewardship, provider education, and clinical decision support tools are recommended to enhance rational drug use and align with WHO standards, especially in resource-limited settings.
Keywords: Drug Utilization Evaluation (DUE); Prescription Pattern Analysis; Polypharmacy; Antibiotic Overuse; Essential Drug List (EDL); Antimicrobial Resistance.